1999
DOI: 10.1111/j.1349-7006.1999.tb00808.x
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic Aspects of Green Tea as a Cancer Preventive: Effect of Components on Human Stomach Cancer Cell Lines

Abstract: It is now well accepted that (−

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
78
0
1

Year Published

1999
1999
2008
2008

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 127 publications
(81 citation statements)
references
References 20 publications
1
78
0
1
Order By: Relevance
“…EGCG inhibited TPA-induced transcriptional activity of NF-kB and its DNA binding in JB6 mouse epidermal cell lines, which could be correlated with the blockage of phosphorylation of IkBa at Ser32 (Nomura et al, 2000). EGCG also inhibited TNF-a gene expression and okadaic acid-induced DNA binding of NF-kB and AP-1 transcriptional factors in KATO III cells (Okabe et al, 1999) and in RAW 264.7 cell lines stimulated with lipopolysaccharides (Yang et al, 1998).…”
Section: Discussionmentioning
confidence: 87%
“…EGCG inhibited TPA-induced transcriptional activity of NF-kB and its DNA binding in JB6 mouse epidermal cell lines, which could be correlated with the blockage of phosphorylation of IkBa at Ser32 (Nomura et al, 2000). EGCG also inhibited TNF-a gene expression and okadaic acid-induced DNA binding of NF-kB and AP-1 transcriptional factors in KATO III cells (Okabe et al, 1999) and in RAW 264.7 cell lines stimulated with lipopolysaccharides (Yang et al, 1998).…”
Section: Discussionmentioning
confidence: 87%
“…EGCG significantly suppressed cancer-invasive ability in oral cancer cell lines by decreasing the number of invasive foci and depth of invasion as strong as classical DNMT inhibitor, 5-aza-dC. Oral administration of green tea has been reported to inhibit tumour genesis in different organs and multiple mechanisms may be involved (Jung and Ellis, 2000;Khan et al, 2006;Chiang et al, 2006;Okabe et al, 1999). Importantly, these effects of EGCG have been shown to be selective for cancer cells, as normal cells were not affected by this treatment (Khan et al, 2006).…”
Section: Discussionmentioning
confidence: 92%
“…However, our data demonstrate that OSCC cell lines-derived MMP-2 and MMP-9 were inhibited at 50 mM of EGCG treatment. Previous studies showed that restored expression of RECK in malignant cells resulted in suppression of invasive activity with concomitant decrease in the secretion of MMPs (Takahashi et al, 1998;Okabe et al, 1999;Liu et al, 2003;Noda et al, 2003). Treatment with EGCG, HSC3 and HSC4 cells cultured on top of collagen gels produced widespread but shallow foci of invasion whereas control cells (EGCG-free medium) invaded and generated large and deep pits extending well in the collagen matrix.…”
Section: Discussionmentioning
confidence: 99%
“…6) However, in a practical sense, it is quantitatively easier to measure inhibition of TNF-a release from cells treated with a tumor promoter such as okadaic acid than inhibition of NFkB activation using a gel mobility shift assay. 7) Based on the study of green tea as cancer preventive agent in the United States 8) and as cancer preventive beverage in Japan, 9) we decided to take a closer look at Japanese herbal medicine for other likely cancer preventives. One classical Japanese herb, Geranium thunbergii SIEB.…”
mentioning
confidence: 99%